THE ISLAMIC PHILANTHROPY MOVEMENT IN INDONESIA: A CONTRIBUTION TO NATION BUILDING AND WORLD SOCIETY - Armiadi Musa; Mohammed, Mustafa Omar (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2024)
This study tries to unravel the contribution of the philanthropic movement in Indonesia in various sectors that have been carried out, both by government, private and voluntary institutions. The method used is to use a juridical normative approach, where data is obtained from secondary data, namely from previous research relevant to this research, as well as a number of fatwas of scholars in the field of muamalah fiqh. The results show that Islamic philanthropy in Indonesia is experiencing significant development, marked by the increasing enthusiasm of the ummah in philanthropy and influenced by the revitalisation of the world vision of Islamic philanthropy, which tries to transform the old paradigm of philanthropy with a new paradigm that is more creative and innovative. A number of solidarity and faith-based national philanthropic institutions have been born, both government-owned, privately-owned and even individually to make a real contribution to strengthening the vision of national development and contributing to the world community